A STUDY TO ASSESS THE EFFECTIVENESS OF VIDEO-ASSISTED PROGRAM ON KNOWLEDGE AND ATTITUDE REGARDING GYNAECOLOGICAL AND BREAST CANCER AMONG WOMEN IN A SELECTED COMMUNITY - Ms. Pavithra.K; Mrs.Jenifar Monisha.A; Prof.Dr.Hema.V.H; Mrs. Eswari .J; Mrs.Kalpana.R; Mrs.Mahizh Punitha.I (The Bioscan, 2026)
The aim of the gynaecological video-assisted and breast cancer video-assisted program is to decrease the number of deaths and to provide the population with the information on the necessity to be more aware. The goals of the program are to avoid risks, offer useful information and raise awareness about the gynaecological and breast cancers to all women in the community. The study objectives included the evaluation of pre- and post-test on knowledge and attitudes in relation to gynaecological and breast cancers affecting women in the sampled community. Another objective of the study was to assess the impact of a video-assisted program on increasing knowledge and attitudes regarding these cancers. Also, the study aimed at correlating the level of knowledge and attitude after the test and determining the impact of the chosen demographic variables on the results.